2016
DOI: 10.24297/ijct.v15i11.4376
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Segmentation of the Heart Ventricles in Short Axis Cardiac Perfusion MRI Images

Abstract: I S S N 2277-3061 V o l u m e 1 5 N u m b e r 1 1 I n t e r n a t i o n a l J o u r n a l o f C o m p u t e r s & T e c h n o l o g y 7 2 1 8 | P a g e c o u n c i l f o r I n n o v a t i v e R e s e a r c h A u g u s t 2 0 1 6 w w w . c i r w o r l d . ABSTRACTCardiovascular diseases (CVDs) cause 31% of the death rate globally. Automatic accurate segmentation is needed for CVDs early detection. In this paper, we study the effect of the registration and initialization of the level set segmentation on the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…No prior study has reported fully automated inline perfusion analysis using deep learning, but efforts had been made to segment perfusion MRI using different algorithms [46][47][48][49][50][51][52][53][54]. An early work [53] was semi-automated by drawing the ROI around heart and applying the GVF snake [55] to segment myocardial border.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No prior study has reported fully automated inline perfusion analysis using deep learning, but efforts had been made to segment perfusion MRI using different algorithms [46][47][48][49][50][51][52][53][54]. An early work [53] was semi-automated by drawing the ROI around heart and applying the GVF snake [55] to segment myocardial border.…”
Section: Discussionmentioning
confidence: 99%
“…An early work [53] was semi-automated by drawing the ROI around heart and applying the GVF snake [55] to segment myocardial border. Other published methods used active contours [51], active shape model [52] and level set based segmentation [46,50,54]. Many works require manual initialization [47][48][49][51][52][53][54] and rely on edge detection from high contrast perfusion phases when contrast agent arrives at LV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation